Review of the ecosystem services of temperate wetlands and their valuation tools - Gill, Laurence (My University, 2022)
Wetlands constitute important habitats that provide several ecosystem services (ES). Wetlands have been termed the kidneys of the world for their water purification services and contain 20–25% of total soil organic carbon. This paper is a review of published studies dealing with the ES of temperate wetlands. Wetlands are among the ecosystems with the most valuable ES, with regulating services being the most important for inland wetlands. While the number of articles on the ES of wetlands has increased exponentially over the past 10 years, more research is needed to achieve a methodological homogenisation in the quantification and valuation of the ES of wetlands. More attention should also be targeted to specific ES of wetlands, and for the geographical distribution of studies. It is also evident that ES have not been valued for some categories of wetlands, such as intermittent karst lakes (poljes/turloughs) which may require more bespoke methodologies to quantify certain aspects of their ES due to their unique annual flooding behaviour.
PUBLISHED
Keywords: Intermittent wetlands; Ecosystem service valuation; Ecosystem services; Temperate wetlands; Smart & Sustainable Planet; ENVIRONMENTAL ENGINEERING